2017
DOI: 10.1016/j.anai.2017.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Baseline asthma burden, comorbidities, and biomarkers in omalizumab-treated patients in PROSPERO

Abstract: ClinicalTrials.gov Identifier: NCT01922037.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 69 publications
1
53
1
Order By: Relevance
“…General characteristics of the twelve included studies that reported on study‐emergent solid epithelial cancer are summarized in Tables and . Additional details can be found in Appendix .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…General characteristics of the twelve included studies that reported on study‐emergent solid epithelial cancer are summarized in Tables and . Additional details can be found in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these studies included a total of 11 758 participants and encompassed three study types. Three were RCTs, one was a comparative observational study (prospective cohort), and eight were non‐comparative observational studies . Their publication dates ranged from 2002 to 2018; however, 75% were published in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…OSA is a well‐known comorbidity of asthma . An important American multicentre real‐life study found prevalence of OSA in omalizumab‐eligible patients being 14.6% . A 2017 large meta‐analysis reported prevalence of OSA in adult asthma patients as 49.5% and the odds of having OSA by asthma patients was 2.64 times higher than in controls .…”
Section: Introductionmentioning
confidence: 99%